The effect of trans-theoretical model stage-matched intervention on medication adherence in hypertensive patients - Saeidi, Kamran; Ghavami, Tina; Shahsavari, Soodeh; Siabani, Soraya; Rajati, Fatemeh (Frontiers in Cardiovascular Medicine, 2024)
IntroductionHypertension is a chronic condition that requires active patient management and awareness of treatment strategies. This study aimed to evaluate the effectiveness of an intervention program grounded in the Transtheoretical Model (TTM) of behavior change for improving treatment adherence among hypertensive patients.Materials and methodsThis study conducted at the Nukan Comprehensive Rural Health Center in Kermanshah, Iran, 120 participants were selected according to specific inclusion criteria. Demographic data and responses to 20 hypertension-related behavior questions were collected via a questionnaire. Participants were categorized into non-adherence (pre-contemplation, contemplation, preparation stages) and adherence categories (action and maintenance stages) based on self-reported medication adherence, with 60 individuals in each group. Each group was then randomly divided into intervention and control subgroups. The educational intervention consisted of four 45 min sessions grounded in TTM constructs regarding to health-related behaviors including Physical activity, salt and oil intake, and fruit and vegetable consumption, and medication adherence. Three months post-intervention, a follow-up questionnaire evaluated the educational impact on treatment adherence. The McNemar test and Chi-square test were utilized to analyze effects across the intervention, control, and pre- and post-intervention groups.ResultsThe participants had a mean age of 58.09 years (SD = 11.85). Three months after the intervention, the non-adherence intervention group showed significant progress in transitioning to the action and maintenance stages across all physical activity behaviors, as well as in salt, oil, fruit and vegetable intake, and medication adherence (P < 0.005). In the adherence intervention group, after the intervention, the number of hypertensive patients who fell into the action and maintenance categories according to all lifestyle variables increased, but the change was not significant. Concerning blood pressure, the intervention group had a significant reduction in mean systolic blood pressure (142.88 ± 20.87 vs. 141.00 ± 18.52; p = 0.015), but the decrease in mean diastolic blood pressure was not significant (88.17 ± 10.30 vs. 87.58 ± 9.70; p = 0.154). No significant changes in systolic or diastolic blood pressure were observed in the control or in intervention groups within the adherence category.ConclusionThis research highlights the potential benefits of applying the TTM to tailor interventions for hypertensive patients with poor treatment adherence, suggesting that such an approach can enhance the efficacy of health education interventions.